2016
DOI: 10.1371/journal.pone.0154056
|View full text |Cite
|
Sign up to set email alerts
|

New Cysteine-Rich Ice-Binding Protein Secreted from Antarctic Microalga, Chloromonas sp.

Abstract: Many microorganisms in Antarctica survive in the cold environment there by producing ice-binding proteins (IBPs) to control the growth of ice around them. An IBP from the Antarctic freshwater microalga, Chloromonas sp., was identified and characterized. The length of the Chloromonas sp. IBP (ChloroIBP) gene was 3.2 kb with 12 exons, and the molecular weight of the protein deduced from the ChloroIBP cDNA was 34.0 kDa. Expression of the ChloroIBP gene was up- and down-regulated by freezing and warming conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…), originally identified as Chlamydomonas but possibly is a species of Chloromonas (Jung et al. ). The amino acid sequences of the type II isoforms have no relation to the type I sequences, although one type II IBP, like the type I IBPs, is predicted to have an ice‐binding face that is rich in threonine residues (Jung et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…), originally identified as Chlamydomonas but possibly is a species of Chloromonas (Jung et al. ). The amino acid sequences of the type II isoforms have no relation to the type I sequences, although one type II IBP, like the type I IBPs, is predicted to have an ice‐binding face that is rich in threonine residues (Jung et al.…”
mentioning
confidence: 99%
“…The amino acid sequences of the type II isoforms have no relation to the type I sequences, although one type II IBP, like the type I IBPs, is predicted to have an ice‐binding face that is rich in threonine residues (Jung et al. ). No other algal type II IBPs exist in any of the databases, while one homolog was found in a bacterium that experiences severe water stress, in which a water‐binding protein could be an advantage (Raymond et al.…”
mentioning
confidence: 99%
“…Cn-AFP, an antifreeze protein from an Antarctic marine diatom, has been studied from a physiological and structural perspective [ 25 , 26 ]. Like other AFPs which have a multiple gene family [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], it was expected that C. neogracile would possess additional isoform AFPs. In this study, we reported a new isoform of C. neogracile AFP gene ( Cn-isoAFP ) and characterized the protein based on biochemical and physiological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ], Chloromonas sp. [ 15 ], and Fragilariopsis sp. [ 16 ], have also been studied using diverse analytic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an IBP from the Antarctic microalga, Chloromonas sp. , has recently been identified that has remarkably similar properties to that seen with plant IBPs, with a low TH (∼ 0.4°C at 5 mg/mL) and hexagonal ice-shaping ( Jung et al, 2016 ). We suggest that IBPs from algal species, such as that described above, may also be good candidates for transgenics.…”
Section: Prospects For the Use Of Ibps For Transgenic Cropsmentioning
confidence: 95%